International branding - Melewar, T.C.; Gupta, Suraksha (Henry Stewart Talks, 2009)
Definition of branding, Ways of branding, Purposes of branding, Types of brands, Brand architecture, Brand experience, Product branding, Corporate branding, Pragmatic shift, Current issues and challenges in international branding